Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Saintifik dalam Pembelajaran Matematika di Madrasah Tsanawiyah - Herawati, Herawati; Erdiansyah, Erdiansyah; Masiah, Masiah (Lembaga Sosial Rumah Indonesia, 2023)
This research aims to produce a valid, practical, and effective student worksheet based on a scientific approach for learning irregular flat-sided spatial figures. The research method used was development research using the Rowntree development model, consisting of three stages: planning, preparation of writing, and development. The practicality of the Student Worksheet (SWD) was assessed through interviews with students during individual evaluations. The practicality evaluation in small group evaluations showed an average score of 4.47, indicating a highly practical category. The effectiveness of the Student Worksheet (SWD) was evident from the improved learning outcomes with an N-gain value of 0.66, falling into the moderate category. This indicates that the Student Worksheet (SWD) has a significant effect on students' learning outcomes. Based on the findings of this research, it is recommended for students and teachers to utilize this Student Worksheet (SWD) in mathematics teaching and learning processes. Furthermore, this research can serve as an additional reference for other researchers in developing teaching materials with other variations, such as using Adobe Flash or Macromedia software.